Three dimensional analysis using finite volume based CFD simulation to determine junction temperature on electronic components / Mazlan Mohamed, Rahim Atan and Mohd Zulkifly Abdullah - Mohamed, Mazlan; Atan, Rahim; Abdullah, Mohd Zulkifly (Universiti Teknologi MARA Pulau Pinang, 2011)
This paper presents the simulation of three dimensional numerical analysis of heat and fluid flow through chip package.